Prophylactic and curative anti-ulcerogenic activity and the possible mechanisms of action of some desert plants - Reham M. El-Meligy; Amani S. Awaad; Gamal A. Soliman; Sanaa A. Kenawy; Saleh I. Alqasoumi (Elsevier, 2017)
The present study aimed to evaluate the anti-ulcerogenic activities and the possible mechanisms of action of seven desert plants from different families. Conyza dioscoridis (L.) Desf. (Asteraceae), Euphorbia hirta L. (Euphorpiaceae), Origanum syriacum L., Salvia lanigera L. (Lamiaceae), Sisymbrium irio L., Solanum nigrum Linn. (Solanaceae) and Solenostemma arghel (Del.) Hayne. (Asclepiadaceae), were tested using prophylactic and curative models of absolute ethanol-induced ulcer, at three doses (125, 250 & 500 mg/kg) of each extract. The investigated extracts possessed dose dependent anti-ulcerogenic activities in both models, with LD50 higher than 5 g/kg. The most effective extracts were C. dioscoridis and S. irio with percent protection of control ulcer; 91.1% and 85.4% respectively. The antisecretory activity of both C. dioscoridis and S. irio appears to be mainly related to the suppression of gastrin release. The in vitro potential radical (DPPH) scavenging activities of the investigated extracts were well supported with the reduction in gastric MDA (50.6% and 43.3%) and enhancing the level of reduced GSH (2.84, 2.59 mg/g tissue) for C. dioscoridis and S. irio respectively. In addition, suppression of the inflammatory mediator TNF-α may be one of the possible mechanisms of action. The alcohol extracts of C. dioscoridis and S. irio showed no alteration on liver and kidney functions. Phytochemical screening of the investigated extracts revealed the presence of flavonoids, tannins and sterols which could be related to the activities.